ChemInform Abstract: Organocatalytic Asymmetric Annulation of 1, 3‐Bis(alkoxycarbonyl)buta‐1, 3‐dienes and Aldehydes. Issue 46 (24th October 2013) - Pezzati, Bernardo; Chellat, Mathieu F.; Murphy, John J.; Besnard, Celine; Reginato, Gianna; Stephens, John C.; Alexakis, Alexandre
Abstract The title reaction proceeds in the presence of an optically active diphenylprolinol derived catalyst to afford cyclohexadienes with excellent diastereo‐ and enantioselectivities.